Effect of Social Media on Medical College Students - Hemant Kumar Halwai (Journal of Universal College of Medical Sciences, 2024)
Social media has transformed medical education, offering various benefits such as access to diverse learning resources, collaboration opportunities, and networking with professionals worldwide. It's indeed a double-edged sword, offering both benefits and drawbacks. On one hand, social media provides a convenient platform for accessing study materials, communicating with peers, and even engaging with instructors and academic resources. It can foster collaboration, critical thinking, and knowledge sharing. Platforms like Twitter work particularly well for delivering journal clubs and Tweetorials because they permit live global participation. Furthermore, it provides a level of informality that makes experts easier to reach, regardless of status or seniority.